Inside Cover: Selective Manipulation of Discrete Mannosidase Activities in the Endoplasmic Reticulum by Using Reciprocally Selective Inhibitors (ChemBioChem 11/2017). (15th May 2017) - Kuribara, Taiki; Hirano, Makoto; Speciale, Gaetano; Williams, Spencer J.; Ito, Yukishige; Totani, Kiichiro
Abstract : The inside cover picture shows inhibitor‐based manipulation of glycoprotein sorting. Several α‐1, 2‐mannosidases in the endoplasmic reticulum (ER) play important roles in producing signal glycoforms that control glyocprotein fate. With 1‐deoxymannojirimycin (dMJ), the glycan was selectively trimmed to the secretion signal in the ER fraction. On the other hand, glycan processing with 1‐deoxynojirimycin (dNJ) selectively produced the degradation signal. Overall, we have demonstrated dMJ and dNJ are available as traffic controllers in glycoprotein quality control. More information can be found in the full paper by K. Totani et al. onpage 979 in Issue 11, 2017 (DOI:10.1002/cbic.201700081 ).